The Effectiveness of Moringa Oleifera in Purifying Pegasius SP Pond Wastewater - Tri Mulyani; Astri Sri Astuti (Universitas Insan Cendekia Mandiri, 2022)
Pond water of silver catfish (Pangasius sp) has high color value, turbidity, and organic compound with the color concentration 250 Pt-Co, turbidity 13.5 NTU, and organic concentration 197.56 mg/L. High concentration of color, turbidity, and organic compound in pond water of silver catfish caused the water should be treated. One of the treatment method is chemical treatment with coagulation-flocculation method. Pond water of silver catfish was treated into clean water using powder of Moringa seed (Moringa oleifera) as organic coagulant using coagulation-flocculation method with Jar-Test system. The aim of this research is to purify water with knowing the removal efficiency of color, turbidity, and organic compound by treating pond water of silver catfish using coagulation-flocculation method and determining optimum dose of coagulant. Jar-Test result showed the color removal efficiency as 86.00% in day 1; 90.75% in day 2; and 88.77% in day 3 with 60 ppm as optimum dose. Turbidity removal efficiency was 84,52% in day 1 and 87.80% in day 2 with 60 ppm as optimum dose. Organic compound removal efficiency was 73.87% in day 1; 77.13% in day 2, and 77.29% in day 3 with 60 ppm as optimum dose.